Dal “crocifisso di Stato” al “crocifisso di classe” (nota a margine di Cass., SS. UU., 9 settembre 2021, n. 24414) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Quadro normativo - 2. Ragionevole accomodamento - 3. Procedimento e soluzioni - 4. Inconvenienti di fatto e prospettive - Appendice.From the “crucifix of State” to the “crucifix of class” (note in margin of Cassation 2021 sept. 9, n. 24414).ABSTRACT: The display of a crucifix in the classrooms is a request furniture by students. In case of dissent by other students or by teachers the headteacher has to search for a mediation, namely a reasonable accomodation, among the conflicting opinions.